The Indonesian government's political economy in the policy of the highest retail price for cooking oil from a sharia perspective - Muhammad Muhsin; Rizka Rizka; Muthoifin Muthoifin (Komunitas Dosen Indonesia, 2023)
Purpose: The phenomenon of a scarcity of cooking oil will occur in Indonesia from the end of 2021 to early 2022, this scarcity will cause prices to rise in markets, causing people to find it difficult to get cooking oil. The Indonesian government, in response to this phenomenon, finally made a policy related to the highest retail price of cooking oil so that the price of cooking oil becomes more stable and easy to reach the public. However, this policy was not welcomed by the public. Therefore this study will discuss the political economy of the Indonesian government in addressing the scarcity of cooking oil from an Islamic perspective. Methodology: This research is descriptive qualitative research, using library research methods by collecting data from literature and books related to the Indonesian government's policy in addressing the scarcity of cooking oil. Results: This study concludes that the scarcity of cooking oil is due to hoarding and an agreement between the four large cooking oil companies to increase their selling price. Government policy in responding to this phenomenon is by Islamic provisions which aim to realize a fair market mechanism. However, there are still many people who think that the purpose of the government policy is bad due to the lack of transparency to the public regarding the policies made by the government